Microbial quality and macronutrient of vermicompost produced by Eisenia fetida in dairy wastewater solids - EULIS TANTI MARLINA; YULI ASTUTI HIDAYATI; ELLIN HARLIA; DEDEN ZAMZAM BADRUZZAMAN; NAOMI MEYNADHEA; NUR ARISTAWIDYA RAHAYU (Society for Indonesian Biodiversity, 2024)
Abstract. Marlina ET, Hidayati YA, Harlia E, Badruzzaman DZ, Meynadhea N, Rahayu NA. 2024. Microbial quality and macronutrient of vermicompost produced by Eisenia fetida in dairy wastewater solids. Biodiversitas 25: 2729-2737. Dairy Wastewater Solids (DWS) contain enough nutrients for the growth of earthworms and utilize the nutritional requirements of livestock waste for growth. The growth of earthworms affects the quality of vermicompost or castings that are useful as organic fertilizers. This research aimed to determine the growth of Eisenia fertida using DWS as a growth medium, and its effect on the quality of vermicompost produced. The organic material decomposed in DWS by indigenous microorganisms and earthworms can convert DWS into organic fertilizer through composting. Rice straw was added as a carbon source to obtain the ideal C/N ratio for the growth of decomposing microorganisms. Good growth of decomposer microorganisms can increase the availability of nutrients in DWS as a source of plant nutrition. E. fetida was used in vermicomposting for 14 days after the initial decomposition phase had passed. This research used the experimental method of Completely Randomized Design (CRD) with three stocking density treatments (T1: 6.6 g/L; T2: 13.3 g/L; T3: 20.0 g/L ) and six replications. The results showed that higher stocking density promoted an increase in the biomass weight of earthworms. Various indigenous microorganisms act as decomposers and work with earthworms to convert organic matter into inorganic matter as a plant nutrient. The stocking density treatment had no significant effect on vermicompost production, total nitrogen content, and P2O5 vermicompost but had a significant effect on K2O, Ca, Mg, population of Nitrogen-Fixing Bacteria (NFB) and Phosphate-Solubilizing Bacteria (PSB). Vermicomposting, DWS, and rice straw mixture produced vermicompost with high functional microbial and macronutrient concentrations.